Формування вищими навчальними закладами конкурентного потенціалу - Чурносова, І. (Схід, 2011)
Конкурентний потенціал вищих навчальних закладів представлений як якісно-кількісні параметри пропозиції. Для обчислення параметрів використано показник "ліцензований прийом". Показана відсутність узгодженості в діях навчальних закладів із формування конкурентного потенціалу. Низький рівень зрілості конкурентних відносин навчальних закладів приводить до безконтрольного зростання сукупної пропозиції. Ця обставина зумовлює загострення конкурентної боротьби на локальному ринку послуг вищої освіти. Competitive potential of higher educational institutions is presented as quality-quantitative parameters of supply. For the calculation of parameters an index "the licensed enrolment" is utilized. Proofs of absence of co-ordination in operating of educational under forming of competition potential are adduced. The low level of maturity of competitive relations of educational establishments results in uncontrolled growth of aggregate supply. This circumstance presupposes of competitive activity intensification local market of services of higher education.